(untitled) (A Luz em Cena: Revista de Pedagogias e Poéticas Cenográficas, 2024)
In the context of the urban aesthetic experience, the audiovisual artistic duo VJ Suave proposes to transform public spaces in an active and dynamic way using the language of light and movement throughout the city. They develop frame-by-frame animation works projected according to the architectural arrangement of the space, illuminating walls, trees, buildings, and other surfaces of the city with projections that emit light, mixing technology with street art. Their works strengthen the connection between the spectator and the city by blending animated stories through moving projections known as light painting with everyday life. To provoke discussion about possible re-significations of the public space of cities, the relationship between the potential articulator between the subject and the urban space is problematized by presenting the work of the collective as a provocateur of transformation of perspectives on the city through light as language and raw material in their works, in order to stimulate the idea of belonging, appropriation, and construction of meaning.